Overview of interventional treatment options for benign prostatic hyperplasia - Elhilali, Mostafa M. (Canadian Medical Association, 2012)
Transurethral resection of the prostate (TURP) remains the gold standard surgical intervention for men with benign prostatic hyperplasia (BPH). However, there are other, newer technologies that have also demonstrated safety and efficacy at least equivalent to that of TURP (e.g., Holmium laser, photoselective vaporization of the prostate). These minimally invasive techniques may be particularly useful for selected patient populations (e.g., those on anticoagulant therapy).